Industrial Solid Wastes and Their Management in Guilan Province - Mohammadnejad, Shahin (Asian Journal of Chemistry, 2010)
Industries, like other waste sources, are associated with numerouswaste-related environmental problems. Guilan province is consideredas an important industrial area in northern Iran. There are ca. 1976industrial units in Guilan province, most of which are located in theoutskirts of cities. In the current study an approximation of the qualityand quantity of the generated waste in food industry of Guilan province,which is recognized as the largest waste generator industry in the studyarea in Iran is provided. In present study, questionnaires were used tocollect data regarding methods of waste management used in 142 of thefood businesses in the area of study. The results of the present researchshow that putrescibles are the most important waste in this industry.The high percentage of putrescibles in the waste stream (73.7 %) andrelatively appropriate physico-chemical characteristics of the waste,suggest the possibility of composting. Additionally, more than 70 % oftotal non-organic wastes is contributed to packaging processes. Thereare relatively few industries that implement such correct waste management.Relatively low price of raw materials and lack of efficient penaltiesin case of inappropriate waste disposal by industries are considered asthe major reasons of such deficiency in regional waste management.It is highly recommended that the implementation of such tax policyaccompanied by joint management of generated industrial wastes beenforced in the area.